Consumer Legal Protection Against Fraud in Ticket Sales Transactions Concerts Through Calo in Indonesia: Case Study of Concert Ticket Sales Fraud - Putri Kamelia; Ade Gunawan (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Concert ticket fraud by irresponsible third parties, such as scalpers, often harms consumers. This research analyzes the legal protection that can be provided to consumers who are victims of concert ticket fraud in Indonesia. The main objective of this research is to enrich understanding of consumer legal protection in the context of concert ticket fraud and encourage the creation of a fairer and safer transaction environment. Through a normative-empirical legal approach, this research examines applicable laws and regulations and cases that have occurred. The research results show that consumers have several options to obtain justice, such as filing a civil lawsuit or choosing non-litigation channels such as mediation or arbitration.